2021
DOI: 10.3390/brainsci11070898
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Acquisition of Concrete and Abstract Words: Behavioural and Electrophysiological Evidence

Abstract: and concrete words differ in their cognitive and neuronal underpinnings, but the exact mechanisms underlying these distinctions are unclear. We investigated differences between these two semantic types by analysing brain responses to newly learnt words with fully controlled psycholinguistic properties. Experimental participants learned 20 novel abstract and concrete words in the context of short stories. After the learning session, event-related potentials (ERPs) to newly learned items were recorded, and acqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 67 publications
2
4
0
1
Order By: Relevance
“…An additional analysis of familiarity ratings (see ) showed that a higher subjective familiarity mirrored the successful acquisition. Our findings are in line with training studies, which induced novel word meaning based on a single training session with concrete versus abstract concepts (Kurmakaeva et al, 2021; Mkrtychian et al, 2021; Palmer et al, 2013). We attribute the participant's high learning success partially to a high motivation and compliance of our sample, based on anecdotal feedback of our participants that the study was “fun.” By establishing a causal link to the linguistic experience, our findings further support the notion that linguistic experience is sufficient for acquiring and thus possibly grounding abstract concepts comparably to how sensorimotor experience forms and grounds concrete concepts (Borghi & Zarcone, 2016; Hoffman, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…An additional analysis of familiarity ratings (see ) showed that a higher subjective familiarity mirrored the successful acquisition. Our findings are in line with training studies, which induced novel word meaning based on a single training session with concrete versus abstract concepts (Kurmakaeva et al, 2021; Mkrtychian et al, 2021; Palmer et al, 2013). We attribute the participant's high learning success partially to a high motivation and compliance of our sample, based on anecdotal feedback of our participants that the study was “fun.” By establishing a causal link to the linguistic experience, our findings further support the notion that linguistic experience is sufficient for acquiring and thus possibly grounding abstract concepts comparably to how sensorimotor experience forms and grounds concrete concepts (Borghi & Zarcone, 2016; Hoffman, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…An additional analysis of familiarity ratings (see Section E in the online supplemental materials) showed that a higher subjective familiarity mirrored the successful acquisition. Our findings are in line with training studies, which induced novel word meaning based on a single training session with concrete versus abstract concepts (Kurmakaeva et al, 2021;Mkrtychian et al, 2021;Palmer et al, 2013). We attribute the participant's high learning success partially to a high motivation and compliance of our sample, based on anecdotal feedback of our participants that the study was "fun."…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Например, в ходе исследования было выявлено, что студенты лучше усваивают значения новых конкретных понятий и словоформы -абстрактных. Это указывает на то, что в обработке и запоминании разных типов семантики, вероятно, участвуют различные механизмы, в том числе и на нейронном уровне (Mkrtychian et al, 2021a). Подтверждением сказанного могут служить обнаруженные различия в ЭЭГ (Mkrtychian et al, 2021b) при усвоении конкретной и абстрактной терминологии, которые проявляются на относительно ранних стадиях (в интервале 136-156 мс) и локализуются в правом полушарии.…”
Section: нейрофизиологические основы формирования профессионального мышления в вузеunclassified